IMPLEMENTASI TINDAK LANJUT OBSERVASI KELAS DENGAN TEKNIK COACHING - Susanti, Nelly; Hendri Yenni, Thasya Dwi; Antoni, Ryan Satria; Anisah, Anisah; Marsidin, Sufyarma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to explain the implementation of coaching in follow-up classroom observations as part of the principal's management. This research was conducted using descriptive qualitative methods. Researchers explain coaching techniques in follow-up efforts to classroom observations as a form of academic supervision. Class observation as a form of academic supervision is part of the principal's management which is the principal's duties and responsibilities. This class observation process is one of a series of teacher performance assessments. The coaching technique is one of the techniques for carrying out follow-up class observations by the school principal. With this technique, classroom observations can increase classroom observation activities which of course have a good impact on learning in general and have an impact on educational progress.